ADP-Dependent Phosphorylation Regulates Association of a DNA-Binding Complex with the Barley Chloroplast psbD Blue-Light-Responsive Promoter - Kim, Minkyun (American Society of Plant Physiologists, 1999)
The chloroplast gene psbD encodes D2, a chlorophyll-binding protein located in the photosystem II reaction center. Transcription of psbD in higher plants involves at least three promoters, one of which is regulated by blue light. The psbD blue-light-regulated promoter (BLRP) consists of a −10 promoter element and an activating complex, AGF, that binds immediately upstream of −35. A second sequence-specific DNA-binding complex, PGTF, binds upstream of AGF between −71 and −100 in the barley (Hordeum vulgare) psbD BLRP. In this study we report that ADP-dependent phosphorylation selectively inhibits the binding of PGTF to the barley psbD BLRP. ATP at high concentrations (1–5 mm) inhibits PGTF binding, but in the presence of phosphocreatine and phosphocreatine kinase, this capacity is lost, presumably due to scavenging of ADP. ADP inhibits PGTF binding at relatively low concentrations (0.1 mm), whereas other nucleotides are unable to mediate this response. ADP-mediated inhibition of PGTF binding is reduced in the presence of the protein kinase inhibitor K252a. This and other results suggest that ADP-dependent phosphorylation of PGTF (or some associated protein) inhibits binding of PGTF to the psbD BLRP and reduces transcription. ADP-dependent phosphorylation is expected to increase in darkness in parallel with the rise in ADP levels in chloroplasts. ADP-dependent phosphorylation in chloroplasts may, therefore, in coordination, inactivate enzymes involved in carbon assimilation, protein synthesis, and transcription during diurnal light/dark cycles.